Artificial Intelligence in Human Resource Management: A Systematic Review of Drivers, Challenges, and Future Pathways - Thulasidoss, Venkatesh; Alfaz, Mohamed; Tamang, Min (Nepal Journal of Multidisciplinary Research, 2025)
Background: In developed countries, recruitment agencies are preferring Artificial Intelligence (AI) technologies in hiring human resources in companies. AI integration has become essential in HRM. AI supports multiple functions such as finding the right employees, setting management goals, maintaining institutional knowledge, and modernising work styles. Objectives: The study aims to examine the role and benefits of AI in HRM, assess the challenges, ethical concerns, and human–AI collaboration, and explore its practical applications and future directions. Method: The research applies literature review as methodology to collect evidences regarding the roles and challenges of AI in the recruitment process through the perspective of the Diffusion of Innovation theory. Findings: Findings shows that AI systems show enhanced efficiency throughout candidate screening processes and skills evaluation however human supervision stands essential to deal with biases and maintain fair recruitment procedures. Conclusion: The research concludes that future recruitment will evolve into human-AI partnership models instead of machine-only automation while proposing industry standards and ethical frameworks and regulatory policies for implementation-guidance. Novelty of the study: Unlike previous research, this paper synthesises how AI development is transforming human resource recruitment while also highlighting the barriers that hinder its effective implementation. A key contribution of this review is the introduction of the concept of human-centered AI in HRM, developed in line with Rogers’ Diffusion of Innovation theory.